PPy / PSf / PEG polymer composite membrane as well as preparation method and application thereof

By using PPy/PSf/PEG polymer composite membrane in the helium separation membrane, and using MOF-derived ZrO2-C nanoparticles and polypyrrole and other technical means, the problem of insufficient flux and selectivity of the existing helium separation membrane is solved, and efficient helium separation and excellent high-temperature and plasticization resistance are achieved.

CN119793231AActive Publication Date: 2025-04-11ZINGKE (CHONGQING) ADVANCED MATERIALS RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510015527.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing helium separation membrane has a low gas flux, a small separation selection coefficient, and a weak high temperature resistance and plasticization resistance, making it difficult to meet the needs of industrial applications.

Method used

The PPy/PSf/PEG polymer composite membrane is used to regulate the polysulfone membrane through MOF derivatization of ZrO2-C nanoparticles, increase the specific surface area and metal active sites, and bind polypyrrole as a conductive polymer to electrodeposit PPy on the PSf surface to improve the stability and interaction of the film, and enhance the hanging film and growth of the PEG solution.

Benefits of technology

High helium flux and selectivity were achieved, the helium flux reached 375GPU, and the selectivity of He/CH4, He/N2, and He/CO2 reached 357, 335, and 379 respectively, which improved the film's high temperature resistance and plasticization resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793231A_ABST
    Figure CN119793231A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer composite materials, in particular to a PPy / PSf / PEG polymer composite membrane and a preparation method and application thereof.The preparation method comprises the steps that a polysulfone membrane is fixed to stainless steel and then clamped to a platinum electrode clamp to serve as a working electrode, and a three-electrode system is constructed; dispersing a pyrrole monomer into deionized water to obtain a first electrolyte, adding the first electrolyte into a sulfuric acid aqueous solution, uniformly mixing, and then adding ZrO2-C nanoparticles to obtain a second electrolyte; placing the three-electrode system in a first electrolyte, depositing for 0.5-1 hour at the current density of 0.4-0.6 mA / cm < 2 >, then placing the three-electrode system in a second electrolyte, depositing for 1.5-3 hours at the current density of 0.1-0.4 mA / cm < 2 >, taking down the electrodeposited polysulfone membrane, cleaning with deionized water, and drying for the first time to obtain a PPy / PSf composite membrane; the PPy / PSf composite membrane is completely soaked in a polyethylene glycol aqueous solution for 3-5 h, then taken out and dried for the second time, and the PPy / PSf / PEG composite membrane is obtained. The PPy / PSf / PEG polymer composite membrane prepared by the preparation method disclosed by the invention has relatively high helium flux and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a PPy / PSf / PEG polymer composite film and a preparation method and application thereof. Background Art

[0002] Natural gas is mainly composed of CH 4 , C 2 H 6 , C 3 H 8 , C 4 H 10 Other hydrocarbon gases, a small amount of CO 2 、N 2 It is composed of non-hydrocarbon gases such as hydrogen, as well as trace to minute amounts of rare gases such as helium. The rare gas helium has special physical properties such as inactive chemical properties, small thermal conductivity and electrical resistance, low melting and boiling points, and easy luminescence. Therefore, it has important industrial uses and application value in aerospace, atomic energy, low-temperature superconductivity, deep diving, laser, electronics, medicine, metallurgy, oil and gas exploration and other fields or industries. Natural gas is the most important source of helium for industrial use. At present, the main technology for helium extraction from natural gas is the cryogenic method. However, the use of cryogenic technology alone for helium purification still has problems such as low operating flexibility, high equipment investment, and high energy consumption. It is not competitive in terms of economic benefits. At the same time, it is difficult to remove hydrogen from the raw gas by the cryogenic method, and the product concentration is difficult to guarantee.

[0003] In recent years, membrane separation has gradually been applied in the field of helium purification. The membrane separation method is driven by the pressure difference on both sides of the membrane, and uses the difference in permeability of each component in the gas during the dissolution, diffusion, and desorption process to achieve the separation effect. The membrane separation method is simple to operate, has low energy consumption, low equipment construction and operation costs, and has high competitiveness. Designing helium separation membranes with high helium selectivity and high gas flux is of great strategic significance for achieving the economy of natural gas helium extraction, reducing dependence on helium imports, and achieving autonomy in helium production and use. Polymer membranes are made of polymers. Ordinary polymer membranes are widely used in gas separation due to their light weight, low cost, and simple preparation process. Organic polymers are easy to synthesize, easy to modify, and have good film-forming properties. However, since organic membranes are not resistant to high pressure, have low mechanical strength, and have poor acid and alkali resistance and thermal stability, they cannot meet industrial applications.

[0004] However, the membrane separation method has very high requirements for helium separation membranes. It must have a high flux and separation selectivity coefficient to purify helium in natural gas, and it must also have excellent high temperature resistance and plasticization resistance. Optimizing the membrane manufacturing process and the preparation of high-performance gas separation membranes are hot topics for further research. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a PPy / PSf / PEG polymer composite membrane and its preparation method and application, so as to at least solve the problems of existing helium separation membranes such as low gas flux, small separation selectivity coefficient, weak high temperature resistance and plasticization resistance.

[0006] The present invention solves the above technical problems by the following technical means:

[0007] A first aspect of an embodiment of the present invention provides a method for preparing a PPy / PSf / PEG polymer composite membrane, comprising the following steps:

[0008] The cleaned and dried polysulfone membrane was fixed on stainless steel with insulating tape, and then clamped on a platinum electrode clamp as a working electrode, a stainless steel sheet as a counter electrode, and a saturated calomel electrode as a reference electrode to construct a three-electrode system.

[0009] The pyrrole monomer was dispersed in deionized water and stirred to obtain a first electrolyte. The first electrolyte was added to a sulfuric acid aqueous solution and mixed. ZrO 2 -C nanoparticles, ultrasonically dispersed to obtain a second electrolyte;

[0010] The three-electrode system is placed in a first electrolyte and the current density is 0.4-0.6 mA / cm 2 The electrolyte was deposited for 0.5 to 1 h and then placed in the second electrolyte at a current density of 0.1 to 0.4 mA / cm 2 After deposition for 1.5 to 3 h, the polysulfone membrane treated by electrodeposition was removed, washed with deionized water, and dried for the first time to obtain a PPy / PSf composite membrane;

[0011] The PPy / PSf composite membrane was completely immersed in a polyethylene glycol aqueous solution for 3 to 5 hours, taken out, and dried for a second time to obtain a PPy / PSf / PEG composite membrane.

[0012] In some embodiments, the concentration of the pyrrole monomer in the first electrolyte is 0.01-0.05 mol / L.

[0013] In some embodiments, the first electrolyte and the aqueous sulfuric acid solution are mixed at a volume ratio of (0.002-0.005):1, and the concentration of sulfuric acid in the aqueous sulfuric acid solution is 0.5 mol / L.

[0014] In some embodiments, the ZrO in the second electrolyte 2 -C nanoparticle concentration is 0.15 ~ 0.5g / L.

[0015] In some embodiments, the ZrO 2 The preparation method of -C nanoparticles is as follows:

[0016] Take terephthalic acid and ZrCl 4 Add to N,N-dimethylformamide, ultrasonically treat for 20 to 30 minutes, add glacial acetic acid, ultrasonically treat for another 20 to 30 minutes, transfer to a hydrothermal reactor, heat at 100 to 120 ° C for 20 to 24 hours, then centrifuge with dimethylformamide and ethanol for precipitation, and dry to obtain UiO-66; UiO-66 is used as a precursor in N 2 Pyrolysis at 750-850℃ for 2-3h under atmosphere to obtain ZrO 2 -C nanoparticles.

[0017] In some embodiments, the terephthalic acid and ZrCl 4 The molar ratio of terephthalic acid to dimethylformamide is 1:(1-1.3), and the molar volume ratio of terephthalic acid to dimethylformamide is 1mmol:(100-200)mL.

[0018] In some embodiments, the concentration of polyethylene glycol in the polyethylene glycol aqueous solution is 2 to 5 wt %.

[0019] In some embodiments, the first drying condition is drying at a temperature of 30-40° C. for 15-24 hours, and the second drying condition is drying in a constant temperature drying oven at a temperature of 50-60° C. and a humidity of 30-40% for 10-15 hours.

[0020] A second aspect of an embodiment of the present invention provides a PPy / PSf / PEG polymer composite membrane, wherein the polymer composite membrane is prepared by the preparation method described in the first aspect.

[0021] A third aspect of the embodiments of the present invention provides application of the PPy / PSf / PEG polymer composite membrane of the second aspect in a helium separation membrane.

[0022] The present invention provides a method for preparing a PPy / PSf / PEG polymer composite membrane, wherein MOF is used to derive ZrO 2 -C nanoparticles are used to regulate the polysulfone membrane, increase the specific surface area and metal active sites of the polysulfone membrane, and improve the separation performance of helium. Polypyrrole (PPy) is selected as the conductive polymer and ZrO is introduced. 2 The deposition of -C nanoparticle electropolymerized PPy on PSf can effectively improve the stability of the membrane, which is beneficial to enhancing the interaction between PSf and PEG, and is more conducive to the formation and growth of PEG solution on the PSf surface.

[0023] The PPy / PSf / PEG polymer composite membrane prepared by the present invention has high helium flux and selectivity. After testing, the helium flux can reach 375GPU, He / CH 4 、He / N 2、He / CO 2 The selectivities can reach 357, 335, and 379 respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the structure of the three-electrode system in the present invention;

[0025] Figure 2 This is a graph showing the anti-plasticization performance test results of the polymer composite film prepared in Example 1;

[0026] Figure 3 This is a graph showing the test results of the anti-plasticization performance of the polymer composite film prepared in Comparative Example 5. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] The terms "first" and "second" in the specification and claims herein are used to distinguish different objects rather than to describe a specific order of objects. In the description of the embodiments of the present application, unless otherwise specified, the meaning of "multiple" refers to two or more, for example, multiple processing units refer to two or more processing units, etc., multiple elements refer to two or more elements, etc.

[0029] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0030] The English meanings in this invention are as follows:

[0031] PPy: polypyrrole; PSf: polysulfone; PEG: polyethylene glycol; SCE: saturated calomel electrode; DMF: N,N-dimethylformamide; Py: pyrrole monomer.

[0032] In order to improve the chemical stability and gas selectivity of the membrane, the present invention proposes a method for preparing a PPy / PSf / PEG polymer composite membrane by deriving ZrO 2-C nanoparticles are used to regulate the polysulfone membrane, increase the specific surface area and metal active sites of the polysulfone membrane, and improve the separation performance of helium. Polypyrrole (PPy) is selected as the conductive polymer and ZrO is introduced. 2 The deposition of -C nanoparticle electropolymerized PPy on PSf can effectively improve the stability of the membrane, which is beneficial to enhancing the interaction between PSf and PEG, and is more conducive to the formation and growth of PEG solution on the PSf surface.

[0033] The preparation method of the PPy / PSf / PEG polymer composite membrane of the present invention comprises the following steps:

[0034] See also Figure 1 ( Figure 1 The cleaned and dried polysulfone membrane was fixed on stainless steel with insulating tape, and then clamped on a platinum electrode clamp as the working electrode, the stainless steel sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode to construct a three-electrode system.

[0035] The pyrrole monomer was dispersed in deionized water and stirred to obtain a first electrolyte. The first electrolyte was added to a sulfuric acid aqueous solution and mixed. ZrO 2 -C nanoparticles, ultrasonically dispersed to obtain a second electrolyte;

[0036] The three-electrode system is placed in a first electrolyte and the current density is 0.4-0.6 mA / cm 2 The electrolyte was deposited for 0.5 to 1 h and then placed in the second electrolyte at a current density of 0.1 to 0.4 mA / cm 2 After deposition for 1.5 to 3 h, the polysulfone membrane treated by electrodeposition was removed, washed with deionized water, and dried for the first time to obtain a PPy / PSf composite membrane;

[0037] The PPy / PSf composite membrane was completely immersed in a polyethylene glycol aqueous solution for 3 to 5 hours, taken out, and dried for a second time to obtain a PPy / PSf / PEG composite membrane.

[0038] The concentration of pyrrole monomer in the first electrolyte is 0.01-0.05 mol / L, and the first electrolyte and the sulfuric acid aqueous solution are mixed in a volume ratio of (0.002-0.005):1, and the sulfuric acid concentration in the sulfuric acid aqueous solution is 0.5 mol / L. 2 -C nanoparticle concentration is 0.15 ~ 0.5g / L.

[0039] Among them, ZrO 2 The preparation method of -C nanoparticles is as follows:

[0040] Take terephthalic acid and ZrCl4 Add to N,N-dimethylformamide, ultrasonically treat for 20 to 30 minutes, add glacial acetic acid, ultrasonically treat for another 20 to 30 minutes, transfer to a hydrothermal reactor, heat at 100 to 120 ° C for 20 to 24 hours, then centrifuge with dimethylformamide and ethanol for precipitation, and dry to obtain UiO-66; UiO-66 is used as a precursor in N 2 Pyrolysis at 750-850℃ for 2-3h under atmosphere to obtain ZrO 2 -C nanoparticles. Among them, terephthalic acid and ZrCl 4 The molar ratio of terephthalic acid to dimethylformamide is 1:(1-1.3), the molar volume ratio of terephthalic acid and dimethylformamide is 1 mmol:(100-200) mL, the concentration of polyethylene glycol in the polyethylene glycol aqueous solution is 2-5 wt%, the first drying condition is drying at a temperature of 30-40° C. for 15-24 h, and the second drying condition is drying in a constant temperature drying oven at a temperature of 50-60° C. and a humidity of 30-40% for 10-15 h.

[0041] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0042] Example 1

[0043] The preparation method of the PPy / PSf / PEG polymer composite membrane of this embodiment is as follows:

[0044] (1) Construction of three-electrode system

[0045] Cut the 2cm 2 The PSf membrane was repeatedly rinsed with deionized water and dried. The surface of the stainless steel sheet was polished with sandpaper, and then repeatedly rinsed with deionized water and ethanol, and dried for later use. The PSf membrane was wrapped and fixed on the stainless steel with electrical insulating tape, and then clamped on the platinum electrode clamp as the working electrode, the stainless steel sheet as the counter electrode, and the saturated calomel electrode as the reference electrode to construct a three-electrode system.

[0046] (2) Preparation of ZrO 2 -C nanoparticles

[0047] Take 1mmol terephthalic acid and 1mmol ZrCl 4 , dissolved in 150ml DMF, ultrasonically treated for 20min, added 20ml glacial acetic acid, ultrasonically treated for 30min, transferred to a hydrothermal reactor, heated at 100℃ for 24h, then centrifuged with DMF and ethanol, and dried at 60℃ in vacuum overnight to obtain UiO-66. 2 The MOF-derived ZrO was obtained by pyrolysis at 800 °C for 2 h under a molten-gas atmosphere.2 -C nanoparticles.

[0048] (3) Preparation of electrolyte

[0049] Disperse the pyrrole monomer into deionized water and stir to obtain a first electrolyte with a pyrrole concentration of 0.04 mol / L. Take 0.14 ml of the first electrolyte and add it to 50 ml of 0.5 mol / L sulfuric acid solution. Stir magnetically for 30 minutes to completely dissolve it. Weigh and add 0.010 g of ZrO 2 -C nanoparticles, and subjected to ultrasonic treatment at room temperature to make them uniformly dispersed, to obtain a second electrolyte.

[0050] (4) Preparation of PPy / PSf composite membrane

[0051] Polypyrrole was deposited on the porous layer of the PSf membrane in two steps by constant current electrochemical method. First, the three-electrode system was placed in the first electrolyte and the current density was 0.5 mA / cm 2 The electrolyte was then placed in the second electrolyte at 0.25 mA / cm 2 The polysulfone membrane treated with electrodeposition was removed and repeatedly washed with deionized water to remove surface pollutants. After washing, it was dried in an oven at 30°C for 20 hours to obtain a PPy / PSf composite membrane.

[0052] (5) Compound with PEG

[0053] Dissolve PEG in deionized water and stir to dissolve at room temperature to prepare a 4 wt% polyethylene glycol aqueous solution. Immerse the PPy / PSf composite membrane of step (4) in the 4 wt% polyethylene glycol aqueous solution. After soaking for 3 hours, remove the free solution on the surface of the membrane and dry the membrane in a constant temperature drying oven at a temperature of 60°C and a humidity of 40% for 10 hours to obtain a PPy / PSf / PEG polymer composite membrane.

[0054] Example 2

[0055] The preparation method of the PPy / PSf / PEG polymer composite membrane of this embodiment is as follows:

[0056] (1) Construction of three-electrode system

[0057] Cut the 2cm 2 The PSf membrane was repeatedly rinsed with deionized water and dried. The surface of the stainless steel sheet was polished with sandpaper, and then repeatedly rinsed with deionized water and ethanol, and dried for later use. The PSf membrane was wrapped and fixed on the stainless steel with electrical insulating tape, and then clamped on the platinum electrode clamp as the working electrode, the stainless steel sheet as the counter electrode, and the saturated calomel electrode as the reference electrode to construct a three-electrode system.

[0058] (2) Preparation of ZrO 2 -C nanoparticles

[0059] Take 1mmol terephthalic acid and 1.2mmol ZrCl 4 , dissolved in 150ml DMF, ultrasonically treated for 25min, added 20ml glacial acetic acid, ultrasonically treated for 20min, transferred to a hydrothermal reactor, heated at 110℃ for 20h, then centrifuged with DMF and ethanol, and dried at 60℃ in vacuum overnight to obtain UiO-66. 2 The MOF-derived ZrO was obtained by pyrolysis at 750 °C for 3 h under a molten-gas atmosphere. 2 -C nanoparticles.

[0060] (3) Preparation of electrolyte

[0061] Disperse the pyrrole monomer in deionized water and stir to obtain a first electrolyte with a pyrrole concentration of 0.01 mol / L. Take 0.10 ml of the first electrolyte and add it to 50 ml of 0.5 mol / L sulfuric acid solution. Stir magnetically for 30 minutes to completely dissolve it. Weigh and add 0.0075 g of ZrO 2 -C nanoparticles, and subjected to ultrasonic treatment at room temperature to make them uniformly dispersed, to obtain a second electrolyte.

[0062] (4) Preparation of PPy / PSf composite membrane

[0063] Polypyrrole was deposited on the porous layer of the PSf membrane in two steps by constant current electrochemical method. First, the three-electrode system was placed in the first electrolyte and then electrochemically charged at a current density of 0.4 mA / cm 2 The electrolyte was then placed in the second electrolyte at 0.1 mA / cm 2 The polysulfone membrane treated with electrodeposition was removed and repeatedly washed with deionized water to remove surface pollutants. After washing, it was dried in an oven at 35°C for 15 hours to obtain a PPy / PSf composite membrane.

[0064] (5) Compound with PEG

[0065] Dissolve PEG in deionized water and stir to dissolve at room temperature to prepare a 2 wt% polyethylene glycol aqueous solution. Immerse the PPy / PSf composite membrane of step (4) in the 2 wt% polyethylene glycol aqueous solution. After soaking for 4 hours, remove the free solution on the surface of the membrane and dry the membrane in a constant temperature drying oven at a temperature of 50°C and a humidity of 30% for 14 hours to obtain a PPy / PSf / PEG polymer composite membrane.

[0066] Example 3

[0067] The preparation method of the PPy / PSf / PEG polymer composite membrane of this embodiment is as follows:

[0068] (1) Construction of three-electrode system

[0069] Cut the 2cm 2 The PSf membrane was repeatedly rinsed with deionized water and dried. The surface of the stainless steel sheet was polished with sandpaper, and then repeatedly rinsed with deionized water and ethanol, and dried for later use. The PSf membrane was wrapped and fixed on the stainless steel with electrical insulating tape, and then clamped on the platinum electrode clamp as the working electrode, the stainless steel sheet as the counter electrode, and the saturated calomel electrode as the reference electrode to construct a three-electrode system.

[0070] (2) Preparation of ZrO 2 -C nanoparticles

[0071] Take 1mmol terephthalic acid and 1.3mmol ZrCl 4 , dissolved in 200 ml DMF, ultrasonically treated for 30 min, added 20 ml glacial acetic acid, ultrasonically treated for 25 min, transferred to a hydrothermal reactor, heated at 120 ° C for 22 h, then centrifuged with DMF and ethanol, and vacuum dried at 60 ° C overnight to obtain UiO-66. 2 The MOF-derived ZrO was obtained by pyrolysis at 850 °C for 2 h under atmosphere. 2 -C nanoparticles.

[0072] (3) Preparation of electrolyte

[0073] Disperse the pyrrole monomer in deionized water and stir to obtain a first electrolyte with a pyrrole concentration of 0.05 mol / L. Take 0.25 ml of the first electrolyte and add it to 50 ml of 0.5 mol / L sulfuric acid solution. Stir magnetically for 30 minutes to completely dissolve it. Weigh and add 0.025 g of ZrO 2 -C nanoparticles, and subjected to ultrasonic treatment at room temperature to make them uniformly dispersed, to obtain a second electrolyte.

[0074] (4) Preparation of PPy / PSf composite membrane

[0075] Polypyrrole was deposited on the porous surface of the PSf membrane in two steps by constant current electrochemical method. First, the three-electrode system was placed in the first electrolyte and the current density was 0.6 mA / cm 2 The electrolyte was then placed in the second electrolyte at 0.4 mA / cm 2 The polysulfone membrane treated with electrodeposition was removed and repeatedly washed with deionized water to remove surface pollutants. After washing, it was dried in an oven at 40°C for 24 hours to obtain a PPy / PSf composite membrane.

[0076] (5) Compound with PEG

[0077] Dissolve PEG in deionized water and stir to dissolve at room temperature to prepare a 5 wt% polyethylene glycol aqueous solution. Immerse the PPy / PSf composite membrane of step (4) in the 5 wt% polyethylene glycol aqueous solution. After soaking for 5 hours, remove the free solution on the surface of the membrane and dry the membrane in a constant temperature drying oven at a temperature of 55°C and a humidity of 35% for 15 hours to obtain a PPy / PSf / PEG polymer composite membrane.

[0078] Comparative Example 1

[0079] The PPy / PSf composite film was prepared in this comparative example. The three-electrode system was constructed and ZrO 2 -C nanoparticles and steps for preparing the electrolyte are the same as those in Example 1, except that:

[0080] Polypyrrole was deposited on the porous surface of the PSf membrane in two steps by constant current electrochemical method. First, the three-electrode system was placed in the second electrolyte and the current density was 0.5 mA / cm 2 The electrolyte was then deposited at 0.25 mA / cm 2 The polysulfone membrane treated with electrodeposition was removed and repeatedly washed with deionized water to remove surface pollutants. After washing, it was dried in an oven at 30°C for 20 hours to obtain a PPy / PSf composite membrane, which was recorded as a PPy / PSf-1-3.5 composite membrane.

[0081] Comparative Example 2

[0082] This comparative example prepares a PPy / PSf composite film. The difference between this comparative example and comparative example 1 is that:

[0083] Polypyrrole was deposited on the porous layer of the PSf membrane in two steps by constant current electrochemical method. First, the three-electrode system was placed in the first electrolyte and the current density was 0.5 mA / cm 2 The electrolyte was then deposited at 0.25 mA / cm 2 The polysulfone membrane treated with electrodeposition was removed and repeatedly washed with deionized water to remove surface pollutants. After washing, it was dried in an oven at 30°C for 20 hours to obtain a PPy / PSf composite membrane, which was recorded as a PPy / PSf-2-3.5 composite membrane.

[0084] Comparative Example 3

[0085] In this comparative example, the ZrO 2-C nanoparticles are replaced with carbon nanotubes. Specifically, the preparation method of the PPy / PSf / PEG polymer composite membrane of this comparative example is as follows:

[0086] (1) Construction of three-electrode system

[0087] Cut the 2cm 2 The PSf membrane was repeatedly rinsed with deionized water and dried. The surface of the stainless steel sheet was polished with sandpaper, and then repeatedly rinsed with deionized water and ethanol, and dried for later use. The PSf membrane was wrapped and fixed on the stainless steel with electrical insulating tape, and then clamped on the platinum electrode clamp as the working electrode, the stainless steel sheet as the counter electrode, and the saturated calomel electrode as the reference electrode to construct a three-electrode system.

[0088] (2) Preparation of electrolyte

[0089] Pyrrole monomer was dispersed in deionized water and stirred to obtain a first electrolyte with a pyrrole concentration of 0.04 mol / L. 0.14 ml of the first electrolyte was added to 50 ml of a 0.5 mol / L sulfuric acid solution and magnetically stirred for 30 min to completely dissolve it. 0.010 g of carbon nanotubes was weighed and added and ultrasonically treated at room temperature to make them dispersed evenly to obtain a third electrolyte.

[0090] (3) Preparation of PPy / PSf composite membrane

[0091] Polypyrrole was deposited on the porous layer of the PSf membrane in two steps by constant current electrochemical method. First, the three-electrode system was placed in the first electrolyte and the current density was 0.5 mA / cm 2 The electrolyte was then placed in the third electrolyte at 0.25 mA / cm 2 The polysulfone membrane treated with electrodeposition was removed and repeatedly washed with deionized water to remove surface pollutants. After washing, it was dried in an oven at 30°C for 20 hours to obtain a PPy / PSf composite membrane.

[0092] (4) Compound with PEG

[0093] Dissolve PEG in deionized water and stir to dissolve at room temperature to prepare a 4 wt% polyethylene glycol aqueous solution. Immerse the PPy / PSf composite membrane of step (3) in the 4 wt% polyethylene glycol aqueous solution. After soaking for 3 hours, remove the free solution on the surface of the membrane and dry the membrane in a constant temperature drying oven at a temperature of 60°C and a humidity of 40% for 10 hours to obtain a PPy / PSf / PEG polymer composite membrane.

[0094] Comparative Example 4

[0095] In this comparative example, a one-step deposition method was used for 3.5 h, and ZrO was not added to the electrolyte.2 -C nanoparticles. Specifically, the preparation method of the PPy / PSf / PEG polymer composite membrane of this embodiment is as follows:

[0096] (1) Construction of three-electrode system

[0097] Cut the 2cm 2 The PSf membrane was repeatedly rinsed with deionized water and dried. The surface of the stainless steel sheet was polished with sandpaper, and then repeatedly rinsed with deionized water and ethanol, and dried for later use. The PSf membrane was wrapped and fixed on the stainless steel with electrical insulating tape, and then clamped on the platinum electrode clamp as the working electrode, the stainless steel sheet as the counter electrode, and the saturated calomel electrode as the reference electrode to construct a three-electrode system.

[0098] (2) Preparation of electrolyte

[0099] The pyrrole monomer was dispersed in deionized water and stirred to obtain a first electrolyte solution with a pyrrole concentration of 0.04 mol / L. 0.14 ml of the first electrolyte solution was added to 50 ml of a 0.5 mol / L sulfuric acid solution and stirred magnetically for 30 minutes to completely dissolve the solution to obtain a fourth electrolyte solution.

[0100] (3) Preparation of PPy / PSf composite membrane

[0101] Polypyrrole was deposited on the porous surface of the PSf membrane in two steps by constant current electrochemical method. The three-electrode system was placed in the third electrolyte and the current density was 0.5 mA / cm 2 After deposition for 3.5 h, the polysulfone membrane treated with electrodeposition was removed, and the surface pollutants were repeatedly washed with deionized water. After washing, it was placed in an oven at 30 °C and dried for 20 h to obtain a PPy / PSf composite membrane.

[0102] (4) Compound with PEG

[0103] Dissolve PEG in deionized water and stir to dissolve at room temperature to prepare a 4 wt% polyethylene glycol aqueous solution. Immerse the PPy / PSf composite membrane of step (4) in the 4 wt% polyethylene glycol aqueous solution. After soaking for 3 hours, remove the free solution on the surface of the membrane and dry the membrane in a constant temperature drying oven at a temperature of 60°C and a humidity of 40% for 10 hours to obtain a PPy / PSf / PEG polymer composite membrane.

[0104] Comparative Example 5

[0105] The PEG / PPy / PSf polymer composite membrane was prepared in this comparative example, and the preparation method thereof is as follows:

[0106] (1) Construction of three-electrode system

[0107] Cut the 2cm 2The PSf membrane was rinsed repeatedly with deionized water. After drying, the PSf membrane was completely immersed in a 4wt% polyethylene glycol aqueous solution. After soaking for 3 hours, the free solution on the membrane surface was removed and the membrane was placed in a constant temperature drying oven at a temperature of 60°C and a humidity of 40% for 10 hours to obtain a PEG / Psf composite membrane. After the surface of the stainless steel sheet was polished with sandpaper, it was repeatedly rinsed with deionized water and ethanol and blown dry for use. The PEG / Psf composite membrane after soaking and drying was wrapped and fixed on the stainless steel with electrical insulating tape, and then clamped on the platinum electrode clamp as the working electrode, the stainless steel sheet as the counter electrode, and the saturated calomel electrode as the reference electrode to construct a three-electrode system.

[0108] (2) Preparation of ZrO 2 -C nanoparticles

[0109] Take 1mmol terephthalic acid and 1mmol ZrCl 4 , dissolved in 150ml DMF, ultrasonically treated for 20min, added 20ml glacial acetic acid, ultrasonically treated for 30min, transferred to a hydrothermal reactor, heated at 100℃ for 24h, then centrifuged with DMF and ethanol, and dried at 60℃ in vacuum overnight to obtain UiO-66. 2 The MOF-derived ZrO was obtained by pyrolysis at 800 °C for 2 h under a molten-gas atmosphere. 2 -C nanoparticles.

[0110] (3) Preparation of electrolyte

[0111] Disperse the pyrrole monomer into deionized water and stir to obtain a first electrolyte with a pyrrole concentration of 0.04 mol / L. Take 0.14 ml of the first electrolyte and add it to 50 ml of 0.5 mol / L sulfuric acid solution. Stir magnetically for 30 minutes to completely dissolve it. Weigh and add 0.010 g of ZrO 2 -C nanoparticles, and subjected to ultrasonic treatment at room temperature to make them uniformly dispersed, to obtain a second electrolyte.

[0112] (4) Preparation of PEG / PPy / PSf polymer composite membrane

[0113] Polypyrrole was deposited on the porous layer of the PEG / Psf composite membrane in two steps by constant current electrochemical method. First, the three-electrode system was placed in the first electrolyte and the current density was 0.5 mA / cm 2 The electrolyte was then placed in the second electrolyte at 0.25 mA / cm 2The PEG / Psf composite membrane treated with electrodeposition was removed and repeatedly washed with deionized water to remove surface pollutants. After washing, it was dried in an oven at 30°C for 20 hours to obtain a PEG / PPy / PSf polymer composite membrane.

[0114] The membranes prepared in Examples 1-3 and Comparative Examples 1-5 were used as test samples and the gas separation performance was tested as follows:

[0115] The polymer composite membranes prepared in Examples 1-3 and Comparative Examples 1-5 were cut and packaged in a module. The test pressure was set to 0.4 MPa and the temperature was set to room temperature. The retentate side and the permeate side were purged with argon. The test gas contained CH 4 , He, CO 2 and N 2 , the test results are shown in Table 1.

[0116]

[0117] Table 1

[0118] The data in Table 1 show that the PPy / PSf / PEG composite membrane of the present invention has high flux and selectivity, and the helium flux can reach 375GPU, He / CH 4 、He / N 2 、He / CO 2 The selectivity can reach 357, 335, and 379, respectively. Comparing the data of Example 1 with that of Comparative Example 2, it can be seen that the helium flux of the PPy / PSf-2-3.5 composite membrane is relatively low, only 131GPU, He / CH 4 The selectivity is only 135, which shows that soaking the composite PEG on the PPy / PSf-2-3.5 composite membrane can effectively improve the helium flux and selectivity of the composite membrane. Compared with the data of Comparative Example 1 and Comparative Example 2, Comparative Example 1 only used one electrolyte for two-step electrolysis, and Comparative Example 2 used two electrolytes for two-step electrolysis, but the helium flux and selectivity of Comparative Example 2 were better than those of Comparative Example 1, which further shows that the choice of electrolyte will also affect the helium flux and selectivity. PPy is first electrodeposited, and then PPy and ZrO are electrolyzed. 2 -C nanoparticles are electrodeposited to improve the helium flux and selectivity of the composite membrane. 2 -C nanoparticles are replaced by carbon nanotubes. The helium flux of Comparative Example 3 is not much different from that of Example 1, but the helium selectivity is poor. It can be seen that ZrO 2 -C nanoparticles can effectively improve the selectivity of helium.

[0119] Using ternary gas mixture He / CO 2 / CH 4 and He / CO 2 / N 2 The anti-plasticization performance of the polymer composite films prepared in Example 1 and Comparative Example 5 was tested. The test results are shown in Figure 2 and Figure 3 .

[0120] Figure 2 This is a graph showing the anti-plasticization performance test results of the polymer composite film prepared in Example 1. Figure 3 This is a graph showing the test results of the anti-plasticization performance of the polymer composite film prepared in Comparative Example 5. Figure 2 It can be seen that with the increase of feed pressure, the helium selectivity does not decrease significantly. Figure 3 The anti-plasticization performance test of the comparative example found that the increase of feed pressure would significantly reduce the helium selectivity and increase the helium flux, indicating that the polymer composite membrane of the comparative example would deviate from the polymer chain in the membrane structure as the pressure increases, thus not having good anti-plasticization performance. 2 -C nanoparticles and Py solution will make the polymer composite film have excellent anti-plasticization properties.

[0121] In summary, the PPy / PSf / PEG polymer composite membrane prepared by the present invention can be used in helium membrane separation and purification.

[0122] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A method for preparing a PPy / PSf / PEG polymer composite membrane, characterized in that: The following steps are involved: The cleaned and dried polysulfone membrane was fixed on stainless steel with insulating tape, and then clamped on a platinum electrode clamp as a working electrode, a stainless steel sheet as a counter electrode, and a saturated calomel electrode as a reference electrode to construct a three-electrode system. Dispersing pyrrole monomer in deionized water, stirring and mixing to obtain a first electrolyte, adding the first electrolyte into a sulfuric acid aqueous solution and mixing, then adding ZrO2-C nanoparticles, and ultrasonically dispersing to obtain a second electrolyte; The three-electrode system is placed in a first electrolyte and the current density is 0.4-0.6 mA / cm 2 The electrolyte was deposited for 0.5 to 1 h and then placed in the second electrolyte at a current density of 0.1 to 0.4 mA / cm 2 After deposition for 1.5 to 3 h, the polysulfone membrane treated by electrodeposition was removed, washed with deionized water, and dried for the first time to obtain a PPy / PSf composite membrane; The PPy / PSf composite membrane was completely immersed in a polyethylene glycol aqueous solution for 3 to 5 hours, taken out, and dried for a second time to obtain a PPy / PSf / PEG composite membrane.

2. The method for preparing a PPy / PSf / PEG polymer composite membrane according to claim 1, characterized in that: The concentration of the pyrrole monomer in the first electrolyte is 0.01-0.05 mol / L.

3. The method for preparing a PPy / PSf / PEG polymer composite membrane according to claim 2, characterized in that: The first electrolyte and the sulfuric acid aqueous solution are mixed in a volume ratio of (0.002-0.005):1, and the sulfuric acid concentration in the sulfuric acid aqueous solution is 0.5 mol / L.

4. The method for preparing a PPy / PSf / PEG polymer composite membrane according to claim 1, characterized in that: The concentration of ZrO2-C nanoparticles in the second electrolyte is 0.15-0.5 g / L.

5. The method for preparing a PPy / PSf / PEG polymer composite membrane according to claim 4, characterized in that: The preparation method of the ZrO2-C nanoparticles is as follows: Terephthalic acid and ZrCl4 were added to N, N-dimethylformamide, and ultrasonically treated for 20 to 30 minutes. Glacial acetic acid was added, and ultrasonically treated for another 20 to 30 minutes. The mixture was transferred to a hydrothermal reactor, and heated at 100 to 120° C. for reaction for 20 to 24 hours. The mixture was then centrifuged and precipitated with N, N-dimethylformamide and ethanol, and dried to obtain UiO-66. Using UiO-66 as a precursor, ZrO2-C nanoparticles were obtained by pyrolysis at 750-850°C for 2-3h in a N2 atmosphere.

6. The method for preparing a PPy / PSf / PEG polymer composite membrane according to claim 5, characterized in that: The molar ratio of the terephthalic acid to ZrCl4 is 1:(1-1.3), and the molar volume ratio of the terephthalic acid to N,N-dimethylformamide is 1mmol:(100-200)mL.

7. The method for preparing a PPy / PSf / PEG polymer composite membrane according to claim 1, characterized in that: The concentration of polyethylene glycol in the polyethylene glycol aqueous solution is 2-5 wt %.

8. The method for preparing a PPy / PSf / PEG polymer composite membrane according to claim 1, characterized in that: The first drying condition is drying at a temperature of 30-40° C. for 15-24 hours, and the second drying condition is drying in a constant temperature drying oven at a temperature of 50-60° C. and a humidity of 30-40% for 10-15 hours.

9. A PPy / PSf / PEG polymer composite membrane, characterized in that: The polymer composite membrane is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the PPy / PSf / PEG polymer composite membrane according to claim 9 in a helium separation membrane.

Citation Information

Patent Citations

  • Preparation method of multi-purpose in-level oil-water separation material

    CN104941458A

  • High-temperature-resistant alkaline water electrolytic bath composite diaphragm and preparation method thereof

    CN114432906A

  • Preparation method of diaphragm for alkaline electrolyzed water

    CN116791144A

  • Proton-conducting membrane and use thereof

    CN1689186A

  • Composite Membranes And Methods For Their Preparation

    US20090001009A1